An Analysis of Positive and Negative Politeness Strategies in the Use of Keigo in Google Maps Reviews of Minato Shokudo - Syifa Nurhaliza Agustiar; Uning Kuraesin (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2026)
This study examines forms of Japanese honorific language (keigo) and positive and negative politeness strategies in keigo-containing customer reviews of Minato Shokudo on Google Maps. Using a pragmatic approach with a qualitative descriptive method, this study is grounded in Penelope Brown & Stephen C. Levinson’s (1987) politeness theory. The data were collected from customer reviews posted between September and December 2025, with the analysis focused on 19 reviews containing keigo. The analysis revealed that a single review may contain multiple forms of keigo as well as positive and negative politeness strategies. The identified forms of keigo include sonkeigo (18 reviews), kenjougo (8 reviews), teineigo (6 reviews), and bikago (9 reviews). Positive politeness strategies were realized through Exaggerate (10 reviews), Give gifts to H (10 reviews), Notice/Attend to H (3 reviews), Offer/Promise (3 reviews), and Be optimistic (1 review). Negative politeness strategies were realized through Give deference (11 reviews), Question/Hedge (9 reviews), Be conventionally indirect (3 reviews), and Impersonalize S and H (1 review). The novelty of this study lies in examining the interrelationship between keigo use and positive and negative politeness strategies in Japanese restaurant online reviews containing keigo, particularly in Google Maps reviews, which have received limited attention in previous studies.